Exploring the role of reinforcement in controlling fatigue crack propagation behavior of perfluorosulfonic-acid membranes. (22nd March 2018) - Zhang, Zhe; Shi, Shouwen; Lin, Qiang; Wang, Lei; Liu, Zheng; Li, Peizhi; Chen, Xu
Abstract: Reinforced composite membranes in polymer-electrolyte fuel cells (PEFCs) are attracting more and more attention due to their simultaneously superior durability and high performance. Despite its improved durability during accelerated stress testing, the underlying mechanism of reinforcement in improving mechanical durability, particularly the crack propagation resistance, has not well been investigated. In this paper, we report the fatigue crack propagation behaviors of reinforced Nafion XL membrane and unreinforced Nafion 212 membrane. It is found that the fatigue crack growth rate of Nafion 212 membrane depends on stress ratios, and that of Nafion XL membrane depends on initial crack length and membrane orientation. In addition, the microstructure changes of reinforced Nafion XL membrane are examined through microscopy studies where two distinct features are observed: crack propagation in outer ionomer layers and interfacial delamination. These two features well explain the distinct fatigue crack propagation behavior of Nafion XL membrane, such as slow and almost constant fatigue crack propagation rate. The findings reported here are not only beneficial for understanding fatigue crack propagation mechanism of reinforced composite membrane but also helpful for designing and optimizing composite ion-conductive membranes. Graphical abstract: Highlights: Fatigue crack propagation rate of reinforced membrane is measured experimentally. Two features characterizing fatigue crack growth of reinforced membrane are found. The mechanism of reinforcement layer in membrane fatigue crack growth is clarified. Ex-situ fatigue crack propagation test could be an alternative to in-situ tests. The impact of reinforcement layer on membrane durability is discussed.